2001
DOI: 10.1002/smj.194
|View full text |Cite
|
Sign up to set email alerts
|

Top manager and network effects on the adoption of innovative management practices: a study of TQM in a public hospital system

Abstract: This paper reports findings from a study that combined two theoretical perspectives—top manager and network/institutional—to examine the factors influencing organizations to adopt innovative management practices. The study setting was a system of public hospitals and the innovation was Total Quality Management (TQM). Study results indicate that both top manager and network/institutional factors are important determinants of whether and when organizations adopt innovations. However, as predicted, the relative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
184
1
19

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(213 citation statements)
references
References 38 publications
9
184
1
19
Order By: Relevance
“…It has been indicated that both top managers and network/institutional perspectives were important for understanding patterns in the adoption of innovations among organizations (Young et al, 2001). While the role of the top manager has been recognized as one of the key variables in the model, the network effect has been considered as well.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been indicated that both top managers and network/institutional perspectives were important for understanding patterns in the adoption of innovations among organizations (Young et al, 2001). While the role of the top manager has been recognized as one of the key variables in the model, the network effect has been considered as well.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that both the top manager and network/institutional factors influence the adoption of new innovation practices such as QM (Young et al, 2001). However, in the context of a single firm, top management is the driving force for quality initiatives (Wilson and Collier, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Health care organizations that incorporate aspects of high performing work systems (HPWS) have been shown to drive employee commitment and job satisfaction (Young et al, 2001), and thereby deliver better quality of patient care (Leggat et al, 2011;McDermott and Keating, 2011). Studies show an inverse link between human resource management practices, infection rates and patient mortality (West et al, 2002;Omar et al 2007;Patterson et al, 2012).…”
Section: People Managementmentioning
confidence: 99%